A13 PROTEINS AND FIBROSTENOTIC CROHN'S DISEASE; WHO SHOWED UP TO THE PARTY?. (15th March 2019) - Lu, C; Dufour, A; Ueno, A; Jijon, H; Prowse, K; Novak, K L; Panaccione, R; Hirota, S A
Abstract: Background: Crohn's Disease (CD) is an inflammatory bowel disease mainly affecting the terminal ileum (TI) with three distinct phenotypes including strictures. Despite advances in medical therapy, fibrostenosis remains a therapeutic challenge as there are no available anti-fibrotic treatments. To date, there are no biomarkers to discriminate stricturing CD from other phenotypes. Early studies suggest that protein biomarkers identified from serum profiling may differentiate CD subtypes, and predict biologic therapy response. However, no studies have assessed which cell surface proteins are found in patients with strictures. Utilizing intestinal ultrasound (US), which readily detects fibrostenotic CD strictures, the serum of patients with and without strictures was collected for proteomic characterization. Aims: To investigate differences in the serum proteome among CD patients with fibrostenosis, as identified on bowel US, to those without strictures. Methods: All consecutive CD patients attending outpatient US appointments received greyscale US. Strictures were defined as a fixed bowel segment with a point of luminal apposition with or without prestenotic dilation. Five patients with ileal strictures were matched with similar ileal CD patients with only inflammatory behaviour, as confirmed on US. Patient sera was collected for quantitative shotgun proteomics using liquid chromatography/mass spectrometry. Statistical analysis was conducted at 1% false discovery rate to identify cell surface proteins to differentiate CD with and without strictures. Results: 10 CD patient samples were collected; five patients allocated to the stricture and five to the non-stricture group. Demographics and age at diagnosis were similar between groups. Mean ileal bowel wall thickness was greater in the strictured (7.5 mm) group than without (4.5mm, p = 0.02). Prestenotic dilation (2 to 5 cm) was present in all with ileal stricture. All patients with a stricture had inflammation (mild/moderate inflammatory fat, hyperemia), while all but one in the non-strictured group had quiescent CD. More than 1, 600 proteins were identified. In the strictured group, 4/5 patients had elevated Plexin-A2 and CD5 antigen-like protein, and 3/5 had elevated neogenin and dystonin. Of the non-strictured patients, 3/5 had elevated MMP-16/MT3-MMP (matrix metalloproteinase 16/membrane-type 3 MMP), and 4/5 had elevated vinculin. Conclusions: The sera of patients with and without structuring CD have a unique protein signature. These results provide an initial foundation driving further evaluation to confirm or refine candidate proteins, comparison to patients with resected strictures, and for mechanistic studies. Protein biomarkers may facilitate early stricture detection, monitor CD progression and ultimately identify patients in need of therapies with the greatest stricture risk. Funding Agencies: None